Predictive Value of SIEV Caliber and Superficial Venous Dominance in Free DIEP Flaps - Sadik, K. W.; Pasko, J.; Cohen, A.; Cacioppo, J. (Journal of Reconstructive Microsurgery, 2013)
Introduction The superficial inferior epigastric vein (SIEV) is recognized as an important potential venous conduit in deep inferior epigastric artery perforator (DIEP) flaps.1234 Diffuse flap congestion, despite a patent deep inferior epigastric venous anastomosis, occurs in 2% of cases. The SIEV can augment venous outflow and decrease flap congestion. Although a poorly understood phenomenon, the likelihood of its use was thought to be directly proportional to the SIEV size and caliber.56 Herein we investigate this correlation.Aim To determine whether the diameter of SIEV in patients undergoing DIEP flaps was predictive of a superficial venous system dominance, necessitating its use in alleviating venous congestion.Patients/Methods The in situ SIEV diameter of 39 sequential patients undergoing DIEP flaps was measured on computed tomography (CT) angiography preoperatively as well as intraoperatively from 2008 to 2009. Three patients were excluded for aborted DIEP flap attempt. Six flaps subsequently required venous outflow augmentation with the SIEV. This data was examined using Spearman's correlation analysis.Results No correlation between SIEV diameter (in situ and radiographic) and eventual use was noted. Other factors such as body mass index (BMI), age, and BMI:SIEV size ratio also failed to predict venous congestion and eventual SIEV use. Flap outcomes are reported herein.Conclusion Our findings suggest that SIEV diameter is not an indicator of superficial epigastric venous dominance and therefore is not predictive of venous congestion nor of its use in increasing venous outflow. This contradicts previously held assumptions that larger caliber SIEVs were indicative of a dominant superficial venous system and more likely to result in their use as an alternate route for venous outflow. Our findings suggest that the SIEV should be prophylactically dissected and harvested in raising every DIEP flap, regardless of its caliber.
Keywords: superficial inferior epigastric vein (SIEV); deep inferior epigastric artery perforator (DIEP); venous system; free flap